2010
DOI: 10.1002/cjoc.201090367
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Poly(diallyldimethylammonium tribromide) as a Novel Polymeric Brominating Agent

Abstract: In this study, the synthesis and applications of a new supported tribromide reagent based on poly(diallyldimethylammonium chloride) is reported. This supported tribromide is used in α-bromoacetalization of ketones, bromination of alkenes and regioselective bromination of activated aromatic compounds. This method is mild and no Br 2 and HBr were used. Other advantages of this reagent are stability, high efficiency, simple filterability and reusability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Hossein et al reported the synthesis and applications of the polymeric tribromide reagent poly(diallyldimethylammonium tribromide) (PDADMATB). 1203 For the preparation of this compound, poly(diallyldimethylammonium bromide) was treated with KBr, followed by oxidation of bromide to bromine with an aqueous solution of oxone (Scheme 425). This supported tribromide was used in α-bromoacetalization of ketones, bromination of alkenes, and regioselective bromination of activated aromatic compounds (Scheme 426).…”
Section: Pyridine and Quinoline Derivatives Of Poly(methyl Methacryla...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hossein et al reported the synthesis and applications of the polymeric tribromide reagent poly(diallyldimethylammonium tribromide) (PDADMATB). 1203 For the preparation of this compound, poly(diallyldimethylammonium bromide) was treated with KBr, followed by oxidation of bromide to bromine with an aqueous solution of oxone (Scheme 425). This supported tribromide was used in α-bromoacetalization of ketones, bromination of alkenes, and regioselective bromination of activated aromatic compounds (Scheme 426).…”
Section: Pyridine and Quinoline Derivatives Of Poly(methyl Methacryla...mentioning
confidence: 99%
“…Hossein et al reported the synthesis and applications of the polymeric tribromide reagent poly(diallyldimethylammonium tribromide) (PDADMATB) . For the preparation of this compound, poly(diallyldimethylammonium bromide) was treated with KBr, followed by oxidation of bromide to bromine with an aqueous solution of oxone (Scheme ).…”
Section: Bromination Reactionsmentioning
confidence: 99%
“…The weakening of the C2 and C3 peaks is because after coating the surface of the paper mulch with AKD, the cellulose on the surface of the paper mulch is covered. Meanwhile, there is a Cl2p peak on the surface of the AKD-coated paper mulch, and the Cl element mainly comes from AKD [65]. All XPS data here have also been corrected for C1s spectra.…”
Section: Sem Analyses Of the Fibre Paper Mulchmentioning
confidence: 99%
“…α-Haloketone acetals are generally prepared via two step strategy involving the α-halogenation of ketones [5] followed by the acetalization of the resulting α-haloketone [6]. Alternatively, one step direct haloacetalization of ketones to α-haloketone acetals has been accomplished using halogenating agents such as Nhalosuccinimide [7], 1,3-dihalo-5,5-dimehtylhydantoin [8], bromine [9], iodobenzene dichloride [10], copper(II)bromide [11], and poly(diallyldimethylammonium chloride) [12].…”
Section: Introductionmentioning
confidence: 99%